106k views
12 votes
Question 3: Solve for x

Question 3: Solve for x-example-1

2 Answers

11 votes

Answer:

-2

Explanation:


{8}^(x + 2) = {32}^(2x + 4)

You need to write this in exponential form with the base of 2:


{2}^(3x + 6) = {2}^(10x + 20)

Then you need to set the exponent s equal:


3x + 6 = 10x + 20

Now we just need to solve it. :)


3x - 10x = 20 - 6


- 7x = 14


x = - 2

That's it. :)

User Artiom  Kozyrev
by
5.1k points
8 votes

Explanation:

the picture shows the answer step by step. make sure to ask if you need any further guidance.

Question 3: Solve for x-example-1
User JnBrymn
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.